Leptin and Adiponectin Signaling Pathways Are Involved in the Antiobesity Effects of Peanut Skin Extract. (14th October 2019) - Xiang, Lan; Wu, Qiaobei; Cheng, Lihong; Sun, Kaiyue; Li, Jing; Yoshida, Minoru; Qi, Jianhua
Abstract : Excessive food intake and metabolic disorder promote obesity and diabetes. In China, peanut skin is used as a herbal medicine to treat hemophilia, thrombocytopenic purpura, and hepatic hemorrhage. In the present study, we demonstrated that peanut skin extract (PSE) safely reduced appetite, body weight, fat tissue, plasma TG and TC, and blood glucose level in mice with diet-induced obesity (DIO). Moreover, the leptin/leptin receptor/neuropeptide Y (NPY) and adiponectin signaling pathways involved in the antiobesity effects of PSE are confirmed through leptin and adiponectin overexpression and leptin receptor silencing in mice . PSE consisted of oligosaccharide and polyphenol in a mass ratio of 45 : 55, and both parts were important for the antiobesity function of PSE. Our results suggested that PSE can be developed as functional medical food to treat metabolic disorders and obesity.